2005
DOI: 10.1536/ihj.46.801
|View full text |Cite
|
Sign up to set email alerts
|

<b>Elevated C-Reactive Protein Levels and Increased Cardiovascular Risk in Patients With Obstructive Sleep Apnea Syndrome</b>

Abstract: SUMMARYObstructive sleep apnea syndrome (OSAS) is associated with cardiovascular morbidity and mortality. Inflammatory processes associated with OSAS may contribute to cardiovascular morbidity in these patients. C-reactive protein (CRP) is an important serum marker of inflammation. We tested the hypothesis that patients with OSAS have increased plasma CRP.After 173 male subjects underwent polysomnography, 94 were considered to have OSAS (apnea-hypopnea index (AHI) > 5), 38 cardiovascular disease (CVD), and 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 26 publications
3
103
0
8
Order By: Relevance
“…It has been suggested that even slight increases in the apnea hypopnea index (AHI) can lead to increased mortality from cardiovascular diseases. Inflammation plays a fundamental role in the development of atherosclerosis (Kokturk et al, 2005), and the inflammatory marker C-reactive protein (CRP) can be used as a potential diagnostic tool. Studies have demonstrated that in individuals with coronary atherosclerotic heart disease, diabetes, hypertension, or those that smoke, CRP is increased as compared with that in the normal population.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that even slight increases in the apnea hypopnea index (AHI) can lead to increased mortality from cardiovascular diseases. Inflammation plays a fundamental role in the development of atherosclerosis (Kokturk et al, 2005), and the inflammatory marker C-reactive protein (CRP) can be used as a potential diagnostic tool. Studies have demonstrated that in individuals with coronary atherosclerotic heart disease, diabetes, hypertension, or those that smoke, CRP is increased as compared with that in the normal population.…”
Section: Introductionmentioning
confidence: 99%
“…The serum CRP levels were significantly higher in the OSA group than in the control group In multiple regression analysis, elevated hs-CRP levels were associated with AHI which was independent of obesity Kokturk et al [20] 94 OSAS patients 57 controls CRP and conventional cardiovascular risk factors such as total cholesterol, low-density lipoprotein, high-density lipoprotein, very low density lipoprotein, and triglycerides CRP levels were significantly elevated in the OSAS group compared to the non-OSAS group CRP levels were independently associated with AHI Shamsuzzaman et al [19] 22 OSAS patients 20 controls CRP CRP levels were independently associated with OSA severity…”
Section: Crpmentioning
confidence: 90%
“…A previous metaanalysis showed PAP therapy to significantly reduce CRP factors such as obesity, other CVDs and medications. Although, several studies have indicated independent associations between CRP levels and OSAS [19][20][21][22][23][36][37][38] , others do not demonstrate significant correlations after adjustment for associated confounding variables [39][40][41][42] . It is possible that OSAS alone may not contribute substantially to CVD since multiple factors have been implicated in the occurrence of CVDs in high-risk patients.…”
Section: Effect Of Positive Airway Pressure Therapy On Levels Of Crpmentioning
confidence: 96%
See 1 more Smart Citation
“…CRP levels have been shown to be higher in patients with OSAS together with cardiovascular diseases compared to those who have OSAS without cardiovascular diseases (14). B-type brain natriuretic peptide (BNP) production from the heart is induced because of the hypoxia and sympathetic discharge.…”
Section: Introductionmentioning
confidence: 99%